2015
DOI: 10.1002/elps.201400608
|View full text |Cite
|
Sign up to set email alerts
|

Comparative proteomic analysis of oil palm leaves infected with Ganoderma boninense revealed changes in proteins involved in photosynthesis, carbohydrate metabolism, and immunity and defense

Abstract: The basidiomycete fungal pathogen Ganoderma boninense is the causative agent for the incurable basal stem rot (BSR) disease in oil palm. This disease causes significant annual crop losses in the oil palm industry. Currently, there is no effective method for disease control and elimination, nor is any molecular marker for early detection of the disease available. An understanding of how BSR affects protein expression in plants may help identify and/or assist in the development of an early detection protocol. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Several studies have shown that soil sterilization can eliminate soil-borne pathogens and promote changes in soil microbe communities that lead to improved plant growth and increased beneficial microbes ( Mahmood et al, 2014 ; Zhang et al, 2016 ; Li et al, 2019 ). However, in our experiment, the soil used did not contain Ganoderma boninense , a fungal pathogen that infects oil palm trees in South East Asia ( Jeffery Daim et al, 2015 ) (ITS data not shown). The benefits of soil sterilization, specifically the elimination of soil-borne pathogens, were therefore not applicable to this experiment.…”
Section: Discussionmentioning
confidence: 89%
“…Several studies have shown that soil sterilization can eliminate soil-borne pathogens and promote changes in soil microbe communities that lead to improved plant growth and increased beneficial microbes ( Mahmood et al, 2014 ; Zhang et al, 2016 ; Li et al, 2019 ). However, in our experiment, the soil used did not contain Ganoderma boninense , a fungal pathogen that infects oil palm trees in South East Asia ( Jeffery Daim et al, 2015 ) (ITS data not shown). The benefits of soil sterilization, specifically the elimination of soil-borne pathogens, were therefore not applicable to this experiment.…”
Section: Discussionmentioning
confidence: 89%
“…A protein expression analysis of Ganoderma -infected oil palm revealed changes in 51 proteins involved in photosynthesis, carbohydrate metabolism, and immunity/defense mechanisms. These findings provide insights into the molecular responses to BSR disease [ 173 ].…”
Section: Research On Detection Methods For Basal Stem Rotmentioning
confidence: 99%
“…Palm oil remains the most efficient oil crop in the world based on its land use (0.36% of the world agricultural land) and productivity (34% of world oils and fats production) [1]. There has been an increasing interest in studying the oil palm proteome to answer many physiological questions, for instance, the machinery of fatty acid production [26], fungal disease affecting the oil palm plantations [7, 8] and the flowering process [9] to enhance the sustainability of oil palm. Our proteomics studies revolved around establishing a quantitative model for oil palm lipid metabolism that would coincide with the biochemical, genomics and transcriptomics analyses.…”
Section: Introductionmentioning
confidence: 99%